Early childhood intervention in Portugal: an overview based on the developmental systems model - Pinto, A. I.; Grande, C.; Aguiar, C.; de Almeida, I. C.; Felgueiras, I.; Pimentel, J.; Serrano, A. M.; Carvalho, L.; Brandão, M. T.; Boavida, T.; Santos, P.; Lopes-dos-Santos, P. (Infants and Young Children, 2012)
Research studies on early childhood intervention (ECI) in Portugal are diffuse regarding both program components and the geographical area under scrutiny. Since the 1990s, a growing body of knowledge and evidence in ECI is being gathered, based on postgraduate teaching, in-service training, and research. This article draws on the systems theory perspective outlined in the Developmental Systems Approach to Early Intervention (M. J. Guralnick, 2001, 2005a, 2011) to (a) depict paradigmatic shifts and scientific evidence, as well as social and political factors, setting the framework for the development of ECI policies and services in Portugal; (b) describe recent Portuguese legislation that established a national ECI system, and deductively analyze its content regarding the structural components of Guralnick's Model; (c) examine the current status of ECI services according to the core principles and components of the Developmental Systems Model. Inspired by M. J. Guralnick's suggestion (2000), the discussion addresses problems at different levels of the system, proposing an agenda for change in ECI in Portugal, underlining the need for the co-construction of a new culture, based on scientific evidence and on in-depth dialogues between researchers, practitioners, and communities.